A spatial hypermedia user interface for intelligent tutoring systems - Verhoeven, Antoon (2009)
Over the past decades, the potential of computers in education has been researched from many different viewpoints. Important approaches are computer aided instruction, intelligent tutoring systems, micro-worlds, epistemic games, and most recently, adaptive hypermedia. Among many theoretical contributions, there has been little consensus on the requirements of the optimal user interface to support computer based education.